Nanoparticles and siRNA: A new era in therapeutics? - María Dolores Pérez-Carrión; Inmaculada Posadas; Valentín Ceña (Elsevier, 2024)
Since its discovery in 1998, the use of small interfering RNA (siRNA) has been increasing in biomedical studies because of its ability to very selectively inhibit the expression of any target gene. Thus, siRNAs can be used to generate therapeutic compounds for different diseases, including those that are currently 'undruggable'. This has led siRNA-based therapeutic compounds to break into clinical settings, with them holding the promise to potentially revolutionise therapeutic approaches. To date, the United States Food and Drug Administration (FDA) have approved 5 compounds for treating different diseases including hypercholesterolemia, transthyretin-mediated amyloidosis (which leads to polyneuropathy), hepatic porphyria, and hyperoxaluria. This current article presents an overview of the molecular mechanisms involved in the selective pharmacological actions of siRNA-based compounds. It also describes the ongoing clinical trials of siRNA-based therapeutic compounds for hepatic diseases, pulmonary diseases, atherosclerosis, hypertriglyceridemia, transthyretin-mediated amyloidosis, and hyperoxaluria, kidney diseases, and haemophilia, as well as providing a description of FDA-approved siRNA therapies. Because of space constraints and to provide an otherwise comprehensive review, siRNA-based compounds applied to cancer therapies have been excluded. Finally, we discuss how the use of lipid-based nanoparticles to deliver siRNAs holds promise for selectively targeting mRNA-encoding proteins associated with the genesis of different diseases. Thus, siRNAs can help reduce the cellular levels of these proteins, thereby contributing to disease treatment. As consequence, a marked increase in the number of marketed siRNA-based medicines is expected in the next two decades, which will likely open up a new era of therapeutics.